The Feminine Condition and Women's Sexual and Reproductive Health in Brazil and France - Silva, Simone Santana da; Fortuna, Cinira Magali; Monceau, Gilles; Soulière, Marguerite; Pilotti, Anne (Frontiers in Psychology, 2022)
Introduction Elements mark the reality of reading the female body in symbolic constructions and social symbols in the exercise of their reproductive health. The study aims to identify elements that characterize the female condition while analyzing the reproductive health of Brazilian and French women. Materials and Methods A qualitative, multicenter, international study was conducted in Brazil and in France between 2016 and 2019. Data were produced through the use of semi-structured scripts. Focus group discussions and individual interviews were conducted with women who gave birth, hetero-female couples who lived the experience of gestation and birth of a baby, and professionals of maternal and childcare services or members of the associations concerned with the health of mothers and babies. It was guided by the theoretical-methodological framework of institutional analysis in line with the French Institutional Socioclinics. Results Sexual and reproductive health in the realities researched in Brazil and France are sometimes close and sometimes far apart. In what involves the Brazilian health system, abortion is criminalized and often performed illegally. Furthermore, pregnancy, childbirth, and the postpartum period are highly medicalized. In addition, childbirth is not assured as an experience for a woman and her family. This aspect is confirmed by high numbers of cesarean sections performed or by maternal and infant mortality indicators. The French health system prioritizes vaginal deliveries and seems to assure more autonomy to women, but at the same time, it is worn out by the logic of profit, the efficiency of actions, and the rationalization of practices. In association with these, there are other intrinsic elements in the functioning of the institution that delineates the format of each country: notion of women's rights, violence against women, and discussion regarding the oppression markers of race, gender, sexuality, and social class. Conclusions Both countries reveal aspects related to the social role of women's bodies. The established logic reflects in the decision to have children, motherhood, women's autonomy over their own bodies, and in the core values linked to the termination of pregnancy and the professional practices developed in prenatal care, childbirth, and postpartum.